Enhancing Economic Growth of Tambelan Through Sea Transportation Development: Implementation of Regional Regulation No. 6, 2012 (Article 14) - Siti Nur Haliza; Widia Ierdiana; Rindi Wulansari; Rizky Octa Putri Charin (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
The traffic system network in the maritime route consists of port arrangements and shipping lanes. Port arrangements can be observed from the quality of infrastructure that supports the loading and discharging activities of people and goods. The purpose of this research is to analyze the implementation of Regional Regulation No. 6 of 2012 Article 14 regarding sea transportation in Tambelan District to enhance the economic growth of the community. This research utilizes the Systemic Dependence theory (Hirschman, 1958), which emphasizes the importance of inter-island connectivity as a crucial factor in reducing dependence on limited resources and fostering inter-island cooperation in sustainable resource development. The research is conducted using a qualitative method. Primary data sources are obtained by collecting and summarizing the results of interviews conducted by the author with informants. The findings indicate that there are still some maritime transportation infrastructures that do not meet port standardization. The community's expectation regarding the addition of fleet ships to establish connectivity between Bintan and Tambelan Districts for more efficient travel time has not been realized yet. This is because the economic needs are still being imported from outside the Tambelan Sub-district area.